Modeling nitrate-contaminated groundwater discharge to the Ria Formosa Coastal Lagoon (Algarve, Portugal) - Hugman, Rui (2018)
A numerical flow and transport model is developed to assess groundwater discharge and nutrient transport to the Ria Formosa coastal lagoon in southern Portugal. A total N load of 350 ton/year is estimated for the considered area, of which agriculture accounts for 73% of total N load, and domestic effluent and atmospheric deposition for the remaining 9% and 18% respectively. Model results suggest that nutrient recycling has led to the high concentrations observed in the Campina de Faro (M12) aquifer, but is still insufficient to account for observed values at the coastline. Furthermore results suggest that even for the best case mitigation scenario, good quality status will not be achieved by 2027, as mandated by the EU Water Framework Directive.